PENDAMPINGAN PENGEMBANGAN WEBSITE PEMERINTAH DESA ROGOMULYO DAN MUKIRAN - ROSA Delima; Argo Wibowo (Politeknik Negeri Sriwijaya, 2020)
Rogomulyo Village and Mukiran Village have a strong desire to provide adequate information and data services. These two villages have many activities and information that are regularly published in the community. Currently, both villages still use paper media and village announcement boards for updating village information. Both villages felt the need to have a website that specifically introduced the village, its potential, and programs owned by the village government and published activities that the village had carried out. To develop village government websites, the Villages of Rogomulyo and Mukiran have problems related to the limited ability of village officials to develop websites and update any information on the web. Digital media use is limited to the use of text messages on messenger applications. For this reason, the two villages need assistance for village website development. Therefore, in this community service activity (PkM), assistance was provided to the two villages in developing the village government website. The approach used in this PkM activity is Participatory Technology Development (PTD). PTD consists of five stages, namely relationship, diagnosis, planning and design, implementation and evaluation, dissemination, and consolidation. All activities are carried out in a participatory manner, where the main actor for each activity is village government officials. Website development is carried out directly by the village government information technology staff accompanied by a service team. The results of the activity are prototypes of the Rogamulyo and Mukiran village government websites that are ready to be published.